Lipidomic fatty acid profile and global gene expression pattern in mammary gland of rats that were exposed to lard-based high fat diet during fetal and lactation periods associated to breast cancer risk in adulthood - Andrade, Fabia de Oliveira; Assis, Sonia de; Jin, Lu; Fontelles, Camile Castilho; Barbisan, Luis Fernando [UNESP]; Purgatto, Eduardo; Hilakivi-Clarke, Leena; Ong, Thomas Prates (Elsevier B.V., 2015)
The persistent effects of animal fat consumption during pregnancy and nursing on the programming of breast cancer risk among female offspring were studied here. We have previously found that female offspring of rat dams that consumed a lard-based high-fat (HF) diet (60% fat-derived energy) during pregnancy, or during pregnancy and lactation, were at a reduced risk of developing mammary cancer. To better understand the unexpected protective effects of early life lard exposure, we have applied lipidomics and nutrigenomics approaches to investigate the fatty acid profile and global gene expression patterns in the mammary tissue of the female offspring. Consumption of this HF diet during gestation had few effects on the mammary tissue fatty acids profile of young adult offspring, while exposure from gestation throughout nursing promoted significant alterations in the fatty acids profile. Major differences were related to decreases in saturated fatty acids (SFA) and increases in omega-6 polyunsaturated fatty acids (PUFAs), monounsaturated fatty acids (MUFAs) and conjugated linolenic acid (CIA) concentrations. In addition several differences in gene expression patterns by microarray analysis between the control and in utero or in utero and during lactation HF exposed offspring were identified. Differential dependency network (DDN) analysis indicated that many of the genes exhibited unique connections to other genes only in the HF offspring. These unique connections included Hrhl-Ythdf1 and Repinl-Elavl2 in the in utero HF offspring, and Rnf213-Htr3b and Klf5-Chrna4 in the in utero and lactation HF offspring, compared with the control offspring. We conclude that an exposure to a lard-based HF diet during early life changes the fatty acid profile and transcriptional network in mammary gland in young adult rats, and these changes appear to be consistent with reduced mammary cancer risk observed in our previous study. (C) 2015 Elsevier Ireland Ltd. All rights reserved.
Keywords: Breast cancer; Animal fat; Fetal programming; Global gene expression; Lipidomic; DDN analysis